Pharmacist Led Assessment of Medication Inappropriateness in a Medicine Department of a Tertiary Care Hospital - Zia, Inamdar Syed; Nandikol, Sunanda; Katragadda, Pradeepthi; Kulkarni, Raghavendra Vinayakarao; Das, Kusal; Kulkarni, Rucha; R, Rashmi; Z, Zulfeqar; G, Gautam (Indian Journal of Pharmacy Practice)
Background and Introduction: Inappropriate use of drugs is a major problem which contributes towards morbidity, mortality and increased length of hospital stay among patient population. Prescription inappropriateness is significant contributor for adverse health and economic outcome and retard quality use of medication among patient population. Objectives: To assess appropriateness of medication prescribed among study population by applying Medication Appropriateness Index (MAI). Methods: A prospective observational study was carried out in medicine department [emergency and general] of a teaching hospital. Patient pertinent and prescription medicine information were reviewed and assessed using medication appropriateness index to intercept medication inappropriateness. Results: Around 1863 drugs were prescribed of which appropriate drugs are found to be 1639 (87.97%) and inappropriate drugs were found to be 424 (22.76%) based on MAI scoring. Out of 424 Inappropriate drugs, 276 (65.17%) were marginally inappropriate, 44 (10.26%) were inappropriate and 104 (24.55%) drugs were with maximal inappropriateness. Polypharmacy was identified as the major factor contributing towards medication inappropriateness 107 (43.145%). Conclusion: The study shows that drug therapy is not consistent on prescribing principles of medicine appropriateness scale and notices the importance and scope of prescriber and patient education. Clinical pharmacist led review of drug therapy assessment can enhance prescribing quality.
Keywords: Medication appropriateness index; Inappropriate prescribing; Likert 3-point scale; Drug-drug interaction; Clinical pharmacist; Polypharmacy.